BETWEEN TWO WORLDS: INDONESIAN NOVICE EFL TEACHERS’ TENSIONS AND NEEDED SUPPORTS DURING PANDEMIC - Wijaya, Alberik Ryan Tendy; Cendra, Anastasia Nelladia (TEFLIN Journal, 2023)
The abrupt changes in the situation and policy caused by the COVID-19 pandemic might dwindle novice teachers’ well-being and add more pressure to their minds that are already clouded with uncertainty. If left untouched, it is more than likely that they would quit teaching entirely. Nevertheless, while challenges, struggles, and tensions experienced by novice EFL teachers have long been studied and well-documented, the novice EFL teachers’ tensions experienced during the pandemic and the supports they need have not been examined. By analyzing guided reflections and interviewing five Indonesian novice EFL teachers, the present research is to answer two questions: 1) What kinds of tensions are experienced by Indonesian novice EFL teachers during the time of the pandemic? 2) What kind of supports do they need to stay in the teaching profession? The result shows that novice teachers experience tensions related to pedagogical-technical, a sense of belonging to the teaching profession, and culture-relationship, which are caused by the abrupt shift to online learning and excessive workload. To mitigate and ease these tensions, needed supports from the government and policymakers, school and school leaders, or colleagues are also discussed.